1975
DOI: 10.1016/s0022-5347(17)66936-2
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Diverticulum

Abstract: Twelve patients with ureteral diverticula encountered in a 25-year period are presented. Although the potential for the development of such lesions may arise from congenital maldevelopments, we believe that in the natural history much depends on the abnormal hydrodynamic states that may be acquired in childhood or adult life. Ureteral diverticula are frequently asymptomatic, requiring no treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Their etiology and their clinical significance are still debated. Barrett and Malek [4], through a series of 12 patients with ureteral diverticulum, showed that associated renal or ureteral diseases may potentiate the development of a diverticulum. Infection has been implicated in causing diverticular formation or, at least, in leading to its discovery [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their etiology and their clinical significance are still debated. Barrett and Malek [4], through a series of 12 patients with ureteral diverticulum, showed that associated renal or ureteral diseases may potentiate the development of a diverticulum. Infection has been implicated in causing diverticular formation or, at least, in leading to its discovery [5].…”
Section: Discussionmentioning
confidence: 99%
“…A nephrectomy is rarely necessary and should only be applied to infected and nonfunctioning kidneys [2,4]. Our patient underwent a diverticular resection with extraction of the stone by open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although many factors have been suggested, the etiology of true congenital ureteral diverticulum remains unknown. Mostly, they appear to be asymptomatic but can also present with recurrent urinary tract infection [4].…”
Section: Discussionmentioning
confidence: 99%
“…Its connection and association with chronic infection of the urinary tract, vesicoureteral reflux, urolithiasis, and perhaps other associated conditions still remains obscure [3]. It may be congenital or acquired [4,5]. We report a case of massive cystic ureteral diverticulum in a 3.5-year-old boy.…”
mentioning
confidence: 96%
“…Ureteric diverticulum rarely causes symptoms in children and is therefore mostly discovered in adults [2]. If symptoms such as abdominal pain or haematuria occur they are usually due to complications such as infection or obstruction of the diverticulum, stone formation or uretero-diverticular reflux [3].…”
Section: Case Reportmentioning
confidence: 99%